Prison Penalty In Providing A Determination Effect For Criminal Actions Of Corruption - Fristia Berdian Tamza (Faculty of Law, Universitas Lampung, 2022)
The case of corruption as a phenomenon of deviation from social, cultural and state life has many scientists and philosophers study and criticize it. One of the world's famous philosophers is Aristotle, who formulated what he calls moral corruption. Moral corruption refers to various forms of the constitution that have deviated so that the regime's rulers are included in the democratic system where by they are no longer led by law, but also on the other hand no longer serv themselves. The problem in this research is the Effectiveness of Imprisonment for Criminal Acts of Corruption, and Does Imprisonment Can Have a Deterrent Effect on Perpetrators of Criminal Acts of Corruption? This paper is a normative legal research. This normative legal research method is used because the approach in this paper is carried out by using a case approach and a statute approach. The prison sentence is threatened for someone who has committed a crime. Imprisonment: consists of life imprisonment and temporary imprisonment or imprisonment for a specific time. The temporary prison sentence is a minimum of one day and a maximum of fifteen years. However, temporary imprisonment may be imposed for twenty years if the crime committed by a person is punishable by death or life imprisonment or is threatened with imprisonment of 20 (twenty) years if there is a combination of several criminal acts (same lop) the perpetrators of criminal acts of corruption deserve death penalty, as such being given the death penalty will provide a deterrent effect and also be a lesson for others not to do the same thing (corruption). Almost no judges generally impose the death penalty because it is associated with aggravating or mitigating reasons. The mitigating factor is far more dominant regarding the highest sentence limit, education, and others.